(3GdJMaI GddWjaI aj JGQjN GdeOjfI GdTQjaIs - (3GdSNGhj , TeS GdOjf eMeO Hf YHO GdQMef Hf eMeO GdSNGhj, GdSNGhj,J (B902 (3g` s ((3YHOGdHGSW Hf YHOGdMajX Hf eMeO Hf TQa GdOjf GdMfai s)
(3ChdgG (B:s
(3GdMeO ddg GdPi TQa GdeMGd hGdGSJbHGd Hef EdjgG gGLQ s
(3BNQgG (B:s
(3JQLeI eMeO Hf eHGQc GdbSWfWjfi hbQC Ydjg GdTaGA SYjO Hf CHj UGdM HGdeOjfI s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B194 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B150s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B84 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs